Drugs that reduce transmission of falciparum malaria. - Price, R; White, N (Elsevier, 2018)
Substantial gains have been made in reducing the global burden of malaria, much of which can be attributed to greater access to prompt diagnosis and highly effective treatment. However, as endemic countries commit to eliminating malaria, more aggressive interventions are needed to target the large number of apparently healthy individuals who harbour transmissible malaria parasites. Although most national antimalarial guidelines recommend artemisinin combination therapy for the management of uncomplicated falciparum malaria, chemopreventive strategies have generally adopted non-artemisinin combination therapy regimens such as sulfadoxinepyrimethamine and amodiaquine. Artemisinin and its derivatives reduce carriage of sexual stages of the malaria parasites (gametocytes) that are infectious to the mosquito vector, but neither artemisinin combination therapies nor sulfadoxine-pyrimethamine and amodiaquine prevent transmission from fully mature Plasmodium falciparum gametocytes that might be present at the time of treatment.